PENINGKATAN MOTIVASI BELAJAR SISWA DI KELAS VIII SMP NEGERI 1 AJUNG MELALUI PRAKTIKUM GLB DAN GLBB - Andi Abdillah; Dinar Maftukh Fajar (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2020)
This research was motivated by the low scores of students SMP Negeri 1 Ajung, Jember, East Java in science subject. Based on the results of an interview with one of the science teachers at SMP Negeri 1 Ajung, students felt difficult in understanding the lessons and completing their assignments. In the initial trial, the implementation of practicum methods in science subject showed the student enthusiasm in the learning process. The purpose of this study was to describe the learning motivation of student grade VIII C SMP Negeri 1 Ajung in science subject before and after practicum of the uniform and accelerated motion; and to describe the increase of learning motivation of student grade VIII C SMP Negeri 1 Ajung through practicum methods in the uniform and accelerated motion. This research used quantitative approach with type of pre-experimental and design of One Group Pretest-Posttest. This research was administered to 32 students and used the paired t test as hypothesis test. The motivation questionnaires, interviews, observations, and tests were used as data collection techniques. The results of hypothesis testing obtained scores of student motivation with t count of 6.01 and t table of 2.04 with a significant level of 5%. This showed a significant increase in learning motivation before and after participating in practicum activities. In addition, the increase of motivation was gained by 7.40%, it was obtained from the difference between the average posttest and pretest results.